Treatment Effect of Mometasone Furoate Cream on Lichen Sclerosus et Atrophicus of External Genitalia in Boys and Its Correlation with Toll-Like Receptor 4 and Myeloid Differentiation Factor 88. (31st March 2022) - Sun, Hong; Zhang, Wei; Wang, Guibo; Sun, Chuanwei; Liang, Yan; Li, Aijun; Li, Qingfeng; Lei, Jie
Abstract : Objective . The objective is to explore the treatment effect of mometasone furoate cream on lichen sclerosus et atrophicus (LSeA) of external genitalia in boys and its correlation with Toll-like receptor 4 (TLR4) and myeloid differentiation factor 88 (MyD88). Methods . A total of 100 boys treated in our hospital from January 2021 to January 2023 due to clinical manifestations in the external genitalia were selected as the study objects. All boys received redundant circumcision treatment, their protein expression of TLR4 and MyD88 in foreskin tissues was measured by BCA protein assay and western blot, and mometasone furoate cream was applied to those who were pathologically diagnosed with LSeA, so as to compare the levels of serum inflammatory factors and urodynamic indicators in the child patients before and after treatment. Results . The total clinical efficacy rate of LSeA child patients was up to 90.79%; after treatment, the maximum and mean urinary flow rates of child patients were significantly higher than before treatment P < 0.001 ; compared with the non-LSeA group, the protein expression of TLR4, MyD88, and NF- κ B was increased in the LSeA group P < 0.001, and the mRNA expression of TLR4, MyD88, and NF- κ B was significantly increased in the LSeA group P < 0.001 ; the results of ROC curves showed that TLR4 had the highest AUC value, and during treatment, the incidence rate of adverse reactions in child patients was 6.58%. Conclusion . LSeA will increase the inflammatory reactions in child patients, and its pathogenesis may be related to the upregulation of TLR4, MyD88, NF- κ B expression and thus activation of TLR4/MyD88/NF- κ B signaling pathways. Applying mometasone furoate cream to LSeA patients after redundant circumcision can effectively reduce the inflammatory reactions in the body and improve their urodynamic indicators, with exact efficacy. Further research will be conducive to establishing a better treatment scheme for such child patients.